Desenvolvimento de modelo de análise relativa do custo associado à tolerância especificada durante a fase de projeto - Zeni, Cristiano (2018)
The fierce market competition encourages automotive industries to go all the way to achieving maximum customer satisfaction with the greatest economic gain possible. Therefore, the process of cost reduction in companies plays a fundamental role. One way to eliminate monetary waste is by optimizing the design tolerance values in mechanical components, which have not been exploited to their full potential. A prospective field research was carried out to evaluate how dimensional engineering is conducted in a large automotive company. It was found that designers make the most use of the experience and knowledge acquired in pastprojects, in order to allocate the tolerances with property, which implies limitations to the developers of product with little time of practice. By examining existing references, it was concluded that despite several studies carried out within this scope, involving analyzes focused on manufacturing losses, control, quality, sustainability and other stages of a product's life cycle, it is noticed that: due to the difficult application of methods, their use by product engineering is still low. Such an effect can be explained by the great complexity of the methods involved, the low adaptability and the excessive amount of input data required, which must be provided by the user. The present study proposes a model of evaluation of the costs of specifying tolerances to assist the designers during the development phase, based on the needs assessed from field research with collaborators of the automotive industry and based on references in the literature. In a comparative and qualitative analysis of the tolerances, in order to serve as a guide for the allocation of values, in a simple and more effective way. From the proposed model, a tool is developed in an electronic spreadsheet, which serves as interface, database and performs the processing for the user. The tool aims at the analysis of the cost of simple parts and the optimization of mechanical assemblies. The model and the tool were verified in two field surveys, with designers and engineers of diverse positions and experiences, through directed tasks and opinion research. One can evaluate that the acceptance of the model and tool were positive and that there is a great chance of its introduction in the day-to-day work by the part of the collaborators. It is evaluated that the work better meets the expectations of designers with less time of experience that having a reference of easy and fast access an specify tolerances with lower cost. However, it is noticed that the adherence of the model and tool no longer shows a tendency so high on the part of the senior employees, since due to their high degree of experience, they can perform a certain part of the operations in an automatic way, without the necessity of a reference.